Tipologi Gender Peserta Program Keluarga Harapan: Studi Di Kabupaten Pesisir Selatan, Kupang, Tulung Agung Dan Gorontalo - Badrun Susantyo; Endah Triati (Indonesia Social Justice Network (ISJN), 2021)
This article aim to understand the gender typology in each location. Its was conducted a combination approach, quantitative and qualitative. By involved 240 respondents and 16 person as informants. This study held in four regions; District of Tulung Agung, Kupang, Pesisir Selatan and Gorontalo. The findings of study indicates that majority of participants program are traditional category/typology, namely feminism and masculine, has reached in 77.5%. This indicated that the pattern of family relationships is still dominated by sexist behavior. The recommendation is, make to ensure that the intervention targets are parallel with the program's target. This means, if the target units of Program Keluarga Harapan is whole of family, make sure all of family members could be participate, icluded the mothers, children and the husband also. Its mean, the PKH could be to build the gender equality in the family also.